2016
DOI: 10.1111/1754-9485.12549
|View full text |Cite
|
Sign up to set email alerts
|

Dermatofibrosarcoma Protuberans: A comprehensive review on the spectrum of clinico‐radiological presentations

Abstract: Dermatofibrosarcoma Protuberans (DFSP) is a rare malignant soft-tissue neoplasm which is often misdiagnosed due to its indolent clinical course and non-specific radiological appearances. An observation case series was conducted with retrospective review of clinical and radiological data of DFSP patients presenting to a major tertiary hospital in Hong Kong for radiological assessment between November 2006 and February 2016. Seven patients with confirmed histological diagnosis of DFSP were included. Tumour sizes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 25 publications
2
11
0
Order By: Relevance
“…2, 3). This is in agreement with Sung et al's results [23]. They observed a characteristic radiological "claw" sign featuring the interface between the lesion and the skin in various imaging modalities, including US, CT, and MRI.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…2, 3). This is in agreement with Sung et al's results [23]. They observed a characteristic radiological "claw" sign featuring the interface between the lesion and the skin in various imaging modalities, including US, CT, and MRI.…”
Section: Discussionsupporting
confidence: 92%
“…Surgical excision of the lesion is the standard treatment for DFSP. Some reports [23] have noted that the recurrence rate after local excision was signi cantly higher than that after wide-margin excision (margins over 3 cm), while the recurrence rate after wide-margin excision was signi cantly higher than that after Mohs surgery. Preoperative US imaging may assist in surgical planning and help to prevent local recurrence.…”
Section: Discussionmentioning
confidence: 92%
“…This is the largest series to date to describe the ultrasound The ultrasound findings for this series of 30 patents are consistent with those described to date. [9][10][11][12][14][15][16] In a study of nine patients with DFSP published in 2013, Lee et al 13 reported round or ovoid tumors with a hypoechoic matrix and small echogenic foci. Although oval lesions, on occasions with lobulated margins, seem to be a consistent ultrasound finding, they are not specific to DFSP, as similar morphologies have been described for other skin lesions such as neurogenic and myxoid tumors, epidermal inclusion cysts, and nodular fascitis.…”
Section: Discussionmentioning
confidence: 99%
“…1 Our ultrasound analysis showed that 20 of the 30 tumors analyzed had finger-like projections extending into the subcutaneous tissue. These projections, which have also been described as a claw sign, 15 a jellyfish-like image, or tentacle-like projections, 16 are a well-recognized ultrasound finding in DFSP, and some authors have even suggested that they should be considered highly suggestive or even pathognomonic for DFSP. 15,16 Correlations have been previously reported between finger-like projections on ultrasound and radial or vertical wedge-shaped extensions of DFSP along the septa on histopathology.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation